Influence of Physical Facilities on Students’ Academic Performance Among Undergraduate Student of Environmental Education, University of Calabar - Nigeria - Comfort Nkongho Agbor; Usang Nkanu Onnoghen; Prince Ololube Nwachukwu; A. E. O. Esu (Mediterranean Journal of Social Sciences, 2022)
The paper examined the influence of physical facilities and academic performance among undergraduate students of Environmental Education, University of Calabar, Calabar-Nigeria. Three research questions and hypotheses was formed by the researchers to achieve the aim of this research. The study made use of ex-post facto research design alongside stratified and simple random sampling techniques. The study population consisted of all the undergraduate students of the Environmental Education Department, University of Calabar; from where a sample of 300 respondents was selected as the sample for the study. A structured questionnaire titled, 'Physical facilities and students’ academic performance (PFSAP) is the instrument utilized in collecting data for the study. The collected data was analyzed with simple regression and multiple regression. The result from the three hypotheses analyzed indicated a significant influence of availability and adequacy of physical facilities on academic performance among undergraduate students in Environmental Education. Sequel to the study findings, a conclusion was reached that availability and adequacy of physical facilities have positive correlation on students’ academic performance. The study recommended that basic facilities should be put in place before commencement of any academic activities; Maintenance culture should be imbibed by the authority so that available physical facilities can stand the test of time; The University should project whatever physical facilities are available during accreditation for government intervention; The alumni of the university should put their resources together to support the university in terms of facilities; and the university should corroborate with other universities with good facilities, within and outside the country for exchange programmes. Received: 29 April 2022 / Accepted: 29 June 2022 / Published: 5 July 2022